Microscopic, biochemical and stable isotopic investigation of seven multi-nutritional food-balls from Indus archaeological site, Rajasthan (India). (June 2021) - Agnihorti, Rajesh; Farooqui, Anjum; Khonde, Niteshkumar; Mathews, Runcie P.; Sharma, Shalini; Gahlaud, S.K.S; Manjul, Sanjay Kumar; Manjul, Arvin; Sawlani, Ravi
Highlights: Seven human made spheroidal balls were found in rural Indus settlement of western India. Microcopic, biochemical and GCMS analyses indicate balls contained plenty of agri-food. Cereals and legumes dominated the composition. Abstract: During excavation of a Harappan archaeological site 4MSR (29°12′24.48″N, 73°09′20.16″E) from western Rajasthan (India), seven closely spaced similar sized spheroids (food-balls) were recovered. Detailed microscopic, biochemical (organic), elemental and stable isotopic composition of the spheroidal-material was studied. δ 13 C value of organic fraction (−22.5‰) indicated agricultural origin of organic matter. Significant excesses of Magnesium (Mg) and Calcium (Ca) and Potassium (K) further supported organic (food material) dominance in the spheroids. Gas chromatography mass-spectrometry (GCMS) analysis showed dominance of plant derived organic compounds in the spheroid sample. Microscopic stain analysis using safranin and iodine dyes confirmed bulk of the spheroids was composed of organic material. Majority of starch granule morphotypes found in spheroid-material were made of legumes and cereals dominated by Mung ( Vigna radiata ). Siliceous phytoliths, Ca and Mg oxalate crystals along with a few Mg sulphate crystals were also observed in spheroids composition. We surmise these spheroids were mainly made up of food grains comprising both cereals and legumes. The concept of offerings for some ritual or multi-nutritive compact food balls for instant nutrition as food-supplement, perhaps prevailing during that period. The presence of bull figurines, hand held copper adze and a Harappan seal in the vicinity of these seven food balls signify that humans revered all these commodities due to their utility and importance to them.